A behavioral signaling explanation for stock splits: Evidence from China - CUI, Chenyu (Institutional Knowledge at Singapore Management University, 2020)
We propose a behavioral signaling explanation for the positive announcement effects of stock splits. There are two key behavioral ingredients in our model. First, (retail) investors have misconceptions about stock splits that make them view stock splits as good news. Second, investors are loss-averse and will be particularly disappointed if a splitting firm’s ex-post performance falls short of expectation. In a separating equilibrium, only managers with favorable private information use stock splits to signal. Using a comprehensive sample of stock splits in China over the period of 1998 to 2017, we find supporting evidence: (1) stock splits elicit positive announcement returns and a higher split ratio is associated with a stronger market reaction; (2) splitting firms have better future operating performance and more favorable analyst forecasts; (3) when future performance is poor, splitting firms experience larger price declines than non-splitting firms; (4) the announcement returns of stock splits are smaller for firms with higher institutional ownership and firms with higher pre-split prices.